Effects of Yeast Fermentation of Corn on Growth Performance, Carcass Characteristic and Meat Quality of Chickens - PHATTANA, Keola; PHOUTHAXAY, Phonesavanh; KANDEE, Thanousinh (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
The aim of the study to evaluate of Corn Meal Fermented with Yeast inThree blooded chicken raising 3 blood lines with the purpose to search for chemical compound changing after corn meal was fermented with yeast. Quality with the growth, composition of carcasses and quality of meat. By using Completely Randomized Design (CRD) and devise 2 step: In step 1: corn meal was fermented with yeast by different time from 0-21 day and In step 2 was selected highest chemical compound to use in a different quantity with 5 treatments and the result showned that: Corn meal that fermented by Yeast in different periods as from 0-21 days was showed that the composition of chemistry as CP, Ash, DM and pH had been changed in a different level of significant when compared with normal corn meal CM at P<0.05, this treatment has higher chemical compound change including protein (CP) as treatment of CM14 next order was CM7. However, when it was compared with other treatments has statistically significant (P<0.05). When CM14 had been taken to mix with other difference feeds, it showed that the feed has quantity corn meal fermented 25% (T3) was the best potential efficiency on growth of chicken 3 blood lines and it has statistically significant by comparing with other treatments and constant that using normal corn powder at (P<0.05) it was showed in the top of weight as g/chicken, added weight (g/chicken) ADG, g/day. Moreover, Treatment (T3) also has been obtained to compound of carcasses better than other treatment even through living weight, weight of warm, weight of carcasses, out chest meat and in chest meat which has statistically significant at (P<0.05) and lowest chemical compound treatment was normal corn meal.When the 3 blood lines chicken was examined the quality of meat from the treatment showed highest quality in among other treatment, This Treatment (T3) presented pH of chest’s meat, pH leg’s meat and possibility of water absorption of meat (chest and leg’s meat) higher than other treatment and constant.